3 sonatas pour piano dédiées au célèbre J. Haydn par L. van Beethoven ... Oeuvre 2, no. 2. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (S. Richault; France; Paris, 2023)
Early edition of the Piano Sonata no. 3 in A major, op. 2, no. 2, published in Paris by S. Richault.